Analysis of laboratory testing results for Chlamydia trachomatis infection in an STI clinic in India: Need for extragenital screening. (April 2017) - Arif, Nazneen; Juyal, Deepak; Sebastian, Sujeesh; Khanna, Neena; Dhawan, Benu
Highlights: Extragenital sites are believed to serve as hidden reservoirs for ongoing transmission of infection. The present study is a retrospective analysis of laboratory data describing characteristics and trends in Chlamydia testing and diagnosis in India. It has been documented that infection rates are high in extra-genital sites irrespective of gender identity. Cases with rectal only infections can be missed if only genital testing is performed. Abstract: Background: Extragenital sites are believed to serve as hidden reservoirs for ongoing transmission of infection. In addition, treatment for rectal Chlamydia infection is different from that of genital Chlamydia infection. Many cases may be missed if only genital testing is performed. Methods: Between September 2015 and August 2016, all male and female attendees at an STI clinic of a tertiary care hospital with genital and or extragenital discharge were screened for CT infection. Samples included endocervical swabs in women, urethral swabs and urine samples in men. Rectal and pharyngeal samples were collected wherever indicated. Results: Of total of 439 samples collected from 417 patients (245 women and 172 men), samples from women had a high positivity rate than men. (13.6% and 11%). High rates of rectal CT was detected nearly 30.43%. All rectal positive cases except one had no concomitant genital infection. Conclusions: Prevalence of extragenital Chlamydia is increasing in men as well as women. What needs to be stressed on is the sexual behaviour of an individual and not the sexual identity. Further studies are needed to help formulate guidelines and recommendations for extragenital screening in a population.